Maintenance and Neuronal Differentiation of Chicken Induced Pluripotent Stem-Like Cells - Rui Dai; Ricardo Rossello; Chun-chun Chen; Joeran Kessler; Ian Davison; Ute Hochgeschwender; Erich D. Jarvis (Hindawi Limited, 2014)
Pluripotent stem cells have the potential to become any cell in the adult body, including neurons and glia. Avian stem cells could be used to study questions, like vocal learning, that would be difficult to examine with traditional mouse models. Induced pluripotent stem cells (iPSCs) are differentiated cells that have been reprogrammed to a pluripotent stem cell state, usually using inducing genes or other molecules. We recently succeeded in generating avian iPSC-like cells using mammalian genes, overcoming a limitation in the generation and use of iPSCs in nonmammalian species (Rosselló et al., 2013). However, there were no established optimal cell culture conditions for avian iPSCs to establish long-term cell lines and thus to study neuronal differentiation in vitro. Here we present an efficient method of maintaining chicken iPSC-like cells and for differentiating them into action potential generating neurons.